The quality of binder-filler interfaces in carbon electrodes - Gary N. Ogden (1995)
The aims of this research project were to identify and classify the binder-filler interfaces formed in carbon electrodes and to determine the effects of the interfacial quality on important electrode properties. The effects of raw materials and some fabrication process variables on interfacial characteristics and quality of laboratory produced test electrodes were also studied, and the development of binder-filler interfaces during the carbonisation process followed. Electrode quality was assessed by measurement of density, electrical resistivity and tensile strength. Pore structural data were also obtained by using a computerised image analysis system allied to an optical microscope. Interface quality data were obtained by examining etched surfaces in a scanning electron microscope and classifying the binder-filler interface observed into one of five categories. The category depending on the extent of contact between the binder and filler. Accordingly, test electrodes were produced from combinations of four filler carbons, comprising three grades of calcined petroleum coke and an electro-calcined anthracite, and four coal-tar binder pitches which varied in the type and quantity of insoluble matter content. Examination of these test electrodes showed that the nature of the filler carbon used had a dominant influence on the quality of the interface formed, as assessed by this technique. A combination of one filler carbon and one binder pitch was used to study the effects of some fabrication process variables. These were pitch content and, mixing time and temperature. Of these process variables, pitch content and mixing temperature were found to have the major effects on the binder-filler interface and electrode quality. Investigation of the development of the binder-filler interfaces during the carbonisation process showed three distinct zones of interface development and transformation. These zones were associated with three temperature dependent mechanisms; thermal stress relaxation between 200-350 degrees C, volatile gas evolution from coal-tar pitch decompositionb etween3 50-600 degrees C and stresses induced by thermal contraction of the binder phase between 600-1000 degrees C.